The social context, communicative language teaching and English language learning in fourth grade students of secondary level at 142 school in San Juan de Lurigancho, 2017 - Veliz Saravia, Paul Pierre (2018)
This study deals with the relationship of the Social Context, Communicative Language Teaching and English Language Learning in fourth grade students of secondary level at 142 School in San Juan de Lurigancho, 2017. This thesis is descriptive-quantitative with a correlational design. The population and sample were 40 fourth grade students who studied English as a subject in a public school. The research was based on determining the relationship between the social context, communicative language teaching and English language learning. After processing and correlating the results taken from a survey, the hypothesis´ results founded to be satisfactory resulting that there was a 95 % of reliability .For this reason the social context has to be thought as an import content into communicative language teaching lessons in order that there is English language learning in foreign students.